Dietary Adherence and Physical Activity: Unraveling the Threads Impacting Blood Pressure in Hypertensive Patients - Dwi Isniarti Amin; Asep Sujana Wahyuri; Roma Irawan; Wilda Welis; Farida Gusni; Dally Rahman; Adri Budiwanto; Yovhandra Ockta (Postgraduate, University of Mataram, 2023)
This study investigates the relationship between dietary adherence, physical activity, and blood pressure among hypertensive patients in the Simpang Pandan Health Center, East Tanjung Jabung Regency. The research, employing quantitative descriptive analysis and a cross-sectional methodology, included 127 hypertensive patients. The results revealed a significant correlation between dietary adherence and blood pressure (p-value=0.000). Of the respondents, 47.2% did not adhere to the recommended diet, while 52.8% showed adherence. Moreover, physical activity demonstrated a substantial association with blood pressure (p-value=0.000). The majority (63.8%) engaged in light physical activity, while 36.2% had heavy physical activity. The study also explored demographic characteristics, noting that 46.5% of respondents were male, and 53.5% were female. The age distribution indicated 39.4% were adults, and 60.6% were elderly. In conclusion, both dietary adherence and physical activity significantly influence blood pressure among hypertensive patients. The findings underscore the importance of maintaining a hypertensive diet, including reduced salt and fatty foods, along with regular physical activity to promote overall health and normalize blood pressure. This research contributes to understanding lifestyle factors impacting hypertensive patients in the Simpang Pandan Health Center, providing insights for healthcare interventions and emphasizing the holistic approach needed for effective hypertension management